The role of the docosahexaenoic acid in nutrition of pregnant and feeding women - Н. М. Шилина (Publishing House TRILIST, 2018)
The article presents information about the properties and functions of the docosahexaenoic acid (DHA) - a long-chain polyunsaturated fatty acid belonging to the ω-3 fatty acid family. DHA, along with the arachidonic acid, is the basic building material for cell membranes of the brain and the visual analyzer. During an active growth of the fetus and baby - in the third trimester of gestation and during breastfeeding - DHA is a conditionally essential fatty acid for the baby and should be provided through the placenta and with maternal breast milk in adequate quantities, which is possible only if the organism of a pregnant and feeding woman has sufficient supply of this fatty acid. According to the recommendations of the international scientific community, women should consume not less than 200 mg of DHA daily during pregnancy and lactation. The evidence of research studies are given, confirming a positive effect of supplementary intake of DHA by pregnant and feeding women on the psychomotor development and visual function of their babies. Advantages of intake of ready forms of DHA by women during pregnancy and lactation have been substantiated.